Pengaruh Kepuasan Terhadap Loyalitas Wisatawan Untuk Menginap Kembali di Homestay Desa Wisata Taro - Mayang Fitri Anggani (Publikasi Indonesia, 2022)
In this research which was conducted in the Taro Tourism Village, that in the Taro Tourism Village as one of the tourist villages that is developing homestays to support the quality of the Tourism Village. Practically, increasing tourist satisfaction to stay at homestays can increase tourist loyalty. It is important for homestay managers to understand the business environment and service marketing conditions to increase tourist satisfaction. Therefore it is necessary to do an analysis of tourist satisfaction at homestays in an effort to increase the loyalty of tourists who stay overnight. The sampling technique in this study was accidental sampling technique, based on ideal sample calculations, this study determined a sample size of 100 people. Methods of data collection using a questionnaire. Methods of data analysis using the classical assumption test, simple linear regression test and the coefficient of determination. The results showed that the variable tourist satisfaction has a positive and significant relationship to loyalty.